2017
DOI: 10.13171/mjc64/01705271612-hamdou
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aluminum corrosion in 0.1 M Na2CO3 by Ricinus communis oil

Abstract: The study was carried out using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) technique. The inhibition efficiency was found around 87 % with 1600 ppm of inhibitor. The efficiency was accentuated with the increase of the concentration while it decreased with the rise of the temperature. Analysis of the polarization curves revealed that the Ricinus communis oil is considered as a mixed inhibitor. The Influence of the temperature was also studied, the values of the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Corrosion parameters obtained from the curves have been given in Table V. The data show that with increasing temperature, the protective effect of the plantain extract on the metal surface decreases, which can be deduced that the extract is physically adsorbed (Fateh et al , 2017; Gaballah et al , 2017; Hamdou et al , 2017). The corrosion current density in the absence and presence of the inhibitor at different temperatures was calculated using equation (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion parameters obtained from the curves have been given in Table V. The data show that with increasing temperature, the protective effect of the plantain extract on the metal surface decreases, which can be deduced that the extract is physically adsorbed (Fateh et al , 2017; Gaballah et al , 2017; Hamdou et al , 2017). The corrosion current density in the absence and presence of the inhibitor at different temperatures was calculated using equation (1).…”
Section: Resultsmentioning
confidence: 99%
“…In the study, they found that the inhibition efficiency is increased with the increase in the concentration and decrease in the temperature. They also found that the inhibitor was the mixed type (Hamdou et al , 2017; Li et al , 2017). El-Etre et al carried out their investigation about effects of the focus extract on steel, nickel and zinc in different environments.…”
Section: Introductionmentioning
confidence: 96%
“…Although phosphates, chromates, dichromates, silicates, bromates and arsenates are popular inorganic inhibitors, their toxic effects on the environment are recognised (Khadraoui et al, 2013). Therefore, the application of non-toxic organic inhibitors is encouraged (Hamdou et al, 2017). The investigations focused on synthesising the environmental friendly chemical compound with low cost which could be used as inhibitors have shown that plant extracts from leaves, seeds, heartwood, bark, roots or fruits inhibit the corrosion of metals in acidic solutions (Khadraoui et al, 2013).…”
Section: Bulletin Of the Chemists And Technologists Of Bosnia And Hermentioning
confidence: 99%
“…Strong electrochemical effects on corrosion of 2xxx alloys may be caused by a more significant change in electrode potential with copper content in solid solution as well as non-uniformities in solid-solution concentration (Davis, 1999). In order to reduce corrosion progress of aluminium alloys in various environments inhibitors are commonly used (Ouchenane et al, 2014, Hamdou et al, 2017, Umoren et al, 2009, Oguzie, 2007, Avwiri et al, 2003, Lamaka et al, 2007, Zheludkevich et al, 2005, Al-Turkustani et al, 2010. The inhibitors retard or prevent the corrosion process by reducing the anodic or cathodic polarisation behaviour (decreasing the value of Tafel coefficients).…”
Section: Introductionmentioning
confidence: 99%